One Side By Himself - Barney, Ronald (Western Experience Series, 2001)
"What an astonishing life and what a remarkable biography. Lewis Barney's sojourn on the hard edge of the American frontier is a forgotten epic. Not only does this book tell of an amazing personal odyssey from his birth in upstate New York in 1808 to his death in Mancos, Colorado, in 1894, but Barney's tale represents a living evocation of some of the most significant themes in American history. Frederick Jackson Turner theorized that the frontier shaped our national character, but Lewis Barney's life stands as a testament to the real impact of the westering experience on a man and his family. Ron Barney's detailed biography of Lewis Barney provides a participant's view of Mormonism's first six decades of controversy, hardship, and triumph, viewed from the bottom of the social heap. Despite his wide-ranging experience and endless sacrifices, Lewis Barney was a worker in the Mormon vineyard, not one of the princes of the Kingdom of God whose lives have been so exhaustively celebrated. Barney's lack of status in this complex hierarchy adds tremendously to the value of this study, since so much nineteenth-century LDS biography has ignored the lives of ordinary people to celebrate a surprisingly small elite whose experiences were far different from those of the general Mormon population." -Will Bagley, editor of the series Kingdom in the West: The Mormons and the American Frontier and editor of The Pioneer Camp of the Saints: The 1846-1847 Mormon Trail Journals of Thomas Bullock.